PENGARUH PROMOSI, PELATIHAN, DAN LINGKUNGAN KERJA NON-FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN BAGIAN TEKNOLOGI INFORMATIKA, TRANSFORMASI BISNIS DAN MANAJEMEN RISIKO - Simatupang, Muda Ibnu Adam; Sasmita, Jumiati; Rama, Rovanita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to find out and analyze the effect of promotion, training, non-physical work environment and job satisfaction of employees of PT. Perkebunan Nusantara III (Persero) Medan Section of Information Technology, Business Transformation and Risk Management. The population in this research is implementing all employees of PT. Perkebunan Nusantara III (Persero) Medan Section of Information Technology, Business Transformation and Risk Management. Sampling techniques total sampling method.Analytical method used is descriptive quantitative methods of analysis. The data used are the primary data and secondary data obtained through the quisitonaires and documentation study of the measurement using the ordinal scale and statistically processed with SPSS program 20.00 for windows. The result of this research show that the promotion variables (), training (), and non-physical work environment (X3) simultaneously positive and significant effect on job satisfaction of employees of PT. Perkebunan Nusantara III (Persero) Medan Section of Information Technology, Business Transformation and Risk Management. Which has indicated by the value of significance 0.000 < 0.05. In a partial can be seen that variable training have influence the most dominant against variable bound satisfaction work are employees of PT. Perkebunan Nusantara III (Persero) Medan Section of Information Technology, Business Transformation and Risk Management. The value of the square = 0.488, adjust r which means 48,8% variable bound described by variable free the remaining 51.2% described by another variable that outside of this research.Keyword : Promotion, Training Non-Physical, Work Environment, Job Satisfaction. Employees of PT. Perkebunan Nusantara III (Persero) Medan Section of Information Technology, Business Transformation and Risk Management.